Idriss Déby and the Darfur conflict - Toïngar, Ésaïe, 1968- (McFarland & Company, Inc., Publishers, 2014)
"The ruler of Chad is the unacknowledged cause of much war and mayhem in central Africa; violence against his people; international counterfeiting; theft of property across the region. Responsible for the Darfur crisis, Deby has not been held accountable by the international community. Déby's transgressions have received little attention, a humanitarian oversight remedied by this work. "--